İş sözleşmesinin işçi tarafından süreli feshi - Yıldız, Elif (My University, 2013)
İşçi ve işveren ihtiyaçlarına uygun türde iş sözleşmesi yapabilirler. İş sözleşmesinin sürekli borç ilişkisi doğuran bir sözleşme olması onun uzun süre devam edeceği anlamına gelmemektedir. Her sözleşme gibi iş sözleşmesi de çeşitli şekillerde sona erebilmektedir. Hukuk sistemi her iki tarafa da tek taraflı olarak iş ilişkisine son verme hakkını tanımıştır. İşte fesih hakkı, hukuken taraflara tanınan, ancak kullanımı bir takım şartlara ve sonuçlara tabi olan bir haktır. Sadece belirsiz süreli iş sözleşmelerinde geçerli olan süreli fesih her iki tarafa da tanınmış bir haktır. “İş Sözleşmesinin İşçi Tarafından Süreli Feshi” başlıklı bu tez çalışması, Türk İş Hukuku kapsamında yer alan iş sözleşmelerinin incelenmesini, buna bağlı olarak da iş sözleşmelerinin sona erme biçimlerini, sona erme biçimlerinden de fesih konusu ve feshe bağlı hukuki sonuçları içermektedir. Üç bölümden oluşan bu çalışmamızın birinci bölümünde iş sözleşmesinin tanımı yapılıp, iş sözleşmesi türleri anlatılmıştır. İkinci bölümde iş sözleşmesinin sona erme biçimlerinden ikale, ölüm ve belirli sürenin bitmesi üzerinde kısaca durulmuştur. Sözleşmenin fesihle sona ermesi, feshin bildirimin hukuki niteliği, içeriği, şekli, yapılma yeri ve zamanı, hüküm doğurma anı ve bildirimli fesih konularını anlatılmıştır. Üçüncü ve son bölümde iş sözleşmesinin işçi tarafından süreli feshinin sonuçları ve fesihle birlikte doğan hak ve borçlar anlatılmıştır. Anahtar Sözcükler: İş hukuku, iş sözleşmesi, süreli fesih

Employees and employers may make an appropriate kind of employment contract according to their requirements. The fact that employment contracts constitute a constant obligation does not also mean that such contracts remain in force for a long time. Employment contracts can also be terminated like other contracts in different ways. Judicial system grants a right for both parties to terminate the employment relation unilaterally. Thereby, the termination right is a legal right of the parties to be exercised subject to some conditions and consequences. The right to terminate the contract by notice, which is merely effective for temporary employment contracts, is a right granted to both parties. This thesis study, namely “Termination of Employment Contracts by Notice by Employee” covers; employment contracts within the scope of Turkish Labor Law, and correspondingly, the types of termination of contracts, termination subjects and legal consequences related to termination. In the first chapter of this study, a definition of employment contracts has been made and kinds of employment contracts have been explained. In the second chapter, termination types of contracts covering; termination agreements, death and termination of employment term have been emphasized shortly. Further topics; termination of contract with termination agreement, legal character of termination notice, its content and format, notification place and time, the moment it becomes effective and termination by notice have also been defined. In the third and the last chapter, the consequences of termination of employment contracts by notice by employee, and rights and obligations born with this termination have been described. labor law, employment contract, termination of term
Keywords: İş Hukuku; İş Sözleşmesi